(untitled) (Research, Society and Development, 2021)
The coronavirus disease required changes in all areas of the world society, forcing all countries to adapt to the new reality. Fighting the virus imposed the need for social isolation, and remote learning became known as the only way to meet the world’s educational demands. Even though it’s an ally, there is still a certain difficulty in dealing with complex issues through remote learning, such as, for example, Genetics contents. This work aimed to know the perceptions of Undergraduates in Biological Sciences of a Federal Institution of Higher Education related to Genetics, as well as its approach through remote teaching. The purchase has an observational nature, with a quali-quantitative approach. As for the objectives, it is classified as exploratory and as for the technical procedures, as field research. The participants agreed to a Free and Informed Consent Form (TCLE) and answered a semi-structured questionnaire, prepared using the Google Forms tool. The results point out different difficulties related to the teaching-learning of Genetics, mainly due to a deficiency in the discussion of these contents in Basic Education and complexities of technical terms inherent to the discipline. Such mishaps are accentuated in the remote period currently experienced, mainly due to the difficulty in conducting practical classes, as well as the implementation of projects that occur in a better contextualization of the Genetics discipline. Thus, we emphasize the need to conduct more studies that mention the influence of remote education in the training of Brazilian teachers and its effects on the quality of teaching in Basic Education.